Influence of Prosolv and Prosolv:Mannitol 200 direct compression fillers on the physicomechanical properties of atorvastatin oral dispersible tablets. (June 2015) - Gowda, Veeran; Pabari, Ritesh M.; Kelly, John G.; Ramtoola, Zebunnissa
Abstract The objective of the present study was to evaluate the influence of Prosolv® and Prosolv®: Mannitol 200 direct compression (DC) fillers on the physicomechanical characteristics of oral dispersible tablets (ODTs) of crystalline atorvastatin calcium. ODTs were formulated by DC and were analyzed for weight uniformity, hardness, friability, drug content, disintegration and dissolution. Three disintegration time (DT) test methods; European Pharmacopoeia (EP) method for conventional tablets (Method 1), a modification of this method (Method 2) and the EP method for oral lyophilisates (Method 3) were compared as part of this study. All ODTs showed low weight variation of <2.5%. Prosolv® only ODTs showed the highest tablet hardness of ∼73 N, hardness decreased with increasing mannitol content. Friability of all formulations was <1% although friability of Prosolv®:Mannitol ODTs was higher than for pure Prosolv®. DT of all ODTs was <30 s. Method 2 showed the fastest DT. Method 3 was non-discriminatory giving a DT of 13–15 s for all formulations. Atorvastatin dissolution from all ODTs was >60% within 5 min despite the drug being crystalline. Prosolv® and Prosolv®:Mannitol-based ODTs are suitable for ODT formulations by DC to give ODTs with high mechanical strength, rapid disintegration and dissolution.